Challenging Empire - Amr G. E. Sabet (International Institute of Islamic Thought, 2006)
The idea for this book emerged from what the author perceives to be the extraordinary post-cold war circumstances associated with the American extremists’ push for empire. Its thesis is simple and straightforward: American unilateralism and militarism have spawned a global social movement against such eventualities, giving rise to a new kind of internationalism. The components of this internationalism are threefold: people and social movements, governments, and the United Nations (UN). Together, rather optimistically or perhaps wishfully, they have come to constitute a “second superpower” capable of challenging this imperial drive (pp. 6 and 257). The book is divided into five chapters. The “Introduction” (chapter 1) presents the thesis and framework of the three-part internationalist perspective. Chapter 2 presents the global social movement as the core component that defies war and empire and that exhibits peoples’ power as the foundation of such defiance. The main argument here is that the events of September 11, 2001, provided a golden opportunity for the George W. Bush administration to manipulate and exploit the American people’s fears and shock. Fear, according to Bennis, undermines “not only independence of will, but the very capacity to think” (p. 31). This was the means by which the neo-conservatives, hijacking state power, were able to carry the American people along, allowing for no serious questioning or opposition. Yet if the United States is ...